2016
DOI: 10.1038/srep23925
|View full text |Cite
|
Sign up to set email alerts
|

Strontium-90 activity concentration in soil samples from the exclusion zone of the Fukushima daiichi nuclear power plant

Abstract: The radioactive fission product 90Sr has a long biological half-life (˜18 y) in the human body. Due to its chemical similarity to calcium it accumulates in bones and irradiates the bone marrow, causing its high radio-toxicity. Assessing 90Sr is therefore extremely important in case of a nuclear disaster. In this work 16 soil samples were collected from the exclusion zone (<30 km) of the earthquake-damaged Fukushima Daiichi nuclear power plant, to measure 90Sr activity concentration using liquid scintillation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…90 Sr and 137 Cs, with half-lives of 29 and 30 years, respectively, are amongst the major by-products from the fission of 235 U (England and Rider, 1993). These isotopes were spread in the environment after the fall-out of the different nuclear weapon detonations, and after the nuclear accidents at Chernobyl (IAEA, 2006) and Fukushima-Daiichi (Sahoo et al, 2016). Because of its capacity to substitute with calcium in the food chain, 90 Sr can disturb ecological systems (Comar et al, 1957).…”
Section: Introductionmentioning
confidence: 99%
“…90 Sr and 137 Cs, with half-lives of 29 and 30 years, respectively, are amongst the major by-products from the fission of 235 U (England and Rider, 1993). These isotopes were spread in the environment after the fall-out of the different nuclear weapon detonations, and after the nuclear accidents at Chernobyl (IAEA, 2006) and Fukushima-Daiichi (Sahoo et al, 2016). Because of its capacity to substitute with calcium in the food chain, 90 Sr can disturb ecological systems (Comar et al, 1957).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that 90 Sr activity concentration in soil and vegetation samples is one to four orders of magnitude lower than that of 137 Cs [12]. Sahoo et al showed that 90 Sr activity concentration in soil from the ex-evacuation zone of the FNPP accident ranged from 3 to 23 Bq/kg, whereas 137 Cs activity concentration ranged from 0.7 to 110 kBq/kg [13], which is consistent with the previous reports [3,10]. The ratio of 90 Sr/ 137 Cs in soil widely varies depending on the area examined.…”
Section: Sr In the Environmentmentioning
confidence: 99%
“…Strontium‐90 together with 137 Cs are major long‐lived radionuclides in spent nuclear fuel and high‐level radioactive wastes . Strontium‐90 is present in surface soil around the world mainly as a result of fallout from past atmospheric nuclear weapons tests, as well as nuclear plant accidents . Moreover, strontium as an element is relatively mobile and can move down with percolating water to underlying layers of soil and into groundwater .…”
Section: Introductionmentioning
confidence: 99%